Automated Lofting-Based Reconstruction of CAD Models from 3D Topology Optimization Results. (April 2022) - Amroune, Abdennour; Cuillière, Jean-Christophe; François, Vincent
Abstract: Topology optimization (TO) has become an integral part of the structural design process in recent years. However, automatically deriving parametrized Computer-Aided Design (CAD) models from TO results still represents a great challenge. In this paper, we present a new fully automatic process aimed at converting 3D TO results that tend towards beam-like structures into solid CAD models. Our reconstruction process starts with curve-skeletonization of the optimized shape. The curve-skeleton obtained is used alongside with a boundary triangulation of the optimized shape to compute closed cross-sections along the skeleton branches and junctions at the intersection between branches. These cross-sections are interpolated with cubic B-spline fitting curves, which are used as a basis for lofting operations to generate CAD surface representations of branches and junctions of the optimized shape. Remaining openings in the optimized shape boundary are closed with filling surfaces. A solid CAD model can be built by sewing together all created surfaces and filling, by the way, the closed boundary that comes out of this process. Finite Element Analysis (FEA) is carried out on both the 3D optimal shape and the CAD solid model derived in order to validate this CAD model. Several case studies are presented to demonstrate effectiveness and usefulness of this new approach. Highlights: Reconstruction of 3D solid models from topology optimization results. Based on curve-skeletonization, B-spline fitting curves and lofting operations. Applied to beam-like topology optimization results. FEA validation of 3D models generated.